New Medieval Literatures 18 (Cambridge Boydell & Brewer, 2018)
An invigorating annual for those who are interested in medieval textual cultures and open to ways in which diverse post-modern methodologies may be applied to them." Alcuin Blamires Review of English Studies"
English
Keywords: Literature & literary studies; literature; European and World literature